Square Talks®: A Mobile App to Support EFL Learners’ Vocabulary Development - Ima Normalia Kusmayanti; Retno Hendryanti (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2021)
In recent years, mobile-based game language learning has proliferated due to its promising prospects and positive impacts in improving teaching and learning outcomes in English vocabulary development. With this phenomenon, Square Talks® was developed specifically to aid EFL beginner learners with their English vocabulary. This study aims to examine the effectiveness of the game app in developing the learners’ English vocabulary development. This study employed a quantitative approach focusing on 34 EFL beginner learners. The focus has been on how effective the game app was statistically and overall experience of using the game app. Data were collected through vocabulary tests and a survey. The test results showed that Square Talks® has improved the subjects’ English vocabulary development with the t-value of the test results is -19.93 indicating a significant effect in increasing the subjects’ English vocabulary development. The survey result revealed positive acceptance toward playing Square Talks® in terms of effectiveness (4.49), usability (4.34), and satisfaction (4.52). Therefore, Square Talks® can be considered to be an alternative learning tool to facilitate EFL beginner learners’ vocabulary development.